Four cytochalasin alkaloids produced by Chaetomium globosum. Issue 19 (7th May 2020) - An, Lin; Li, Cui-Ping; Zhang, Hong; Wang, Ming-Ling; Kong, Ling-Yi; Yang, Ming-Hua
Graphical abstract: Highlights: Compound 1 was a novel aureonitol derivative fused to the chaetoglobosin moiety via [4 + 2] cycloaddition. Compounds 2 –4 were three new chaetoglobosins. They exhibited moderate cytotoxic activities against HepG2 and U-2OS cell lines. Abstract: A new adduct of chaetoglobosin and aureonitol derivative, aureochaeglobosin D, with three new alkaloids cytoglobosin J-L were isolated from the solid culture of an endophytic Chaetomium globosum harbored in Pinellia ternata . The structures were elucidated by detailed spectroscopic analysis. Their absolute configurations were determined by the modified Mosher's method and the Rh2 (OCOCF3 )4 -induced electronic circular dichroism (ECD) experiment. These compounds exhibited moderate activities with IC50 values in the range of 11–37 µM when evaluating cytotoxic effects against MDA-MB-231, HepG2 and U-2OS cell lines.